2024
DOI: 10.14791/btrt.2023.0044
|View full text |Cite
|
Sign up to set email alerts
|

Awake Surgery for Angiocentric Glioma in the Eloquent Area in an Adolescent: A Case Report

Yuma Yano,
Ryosuke Matsuda,
Fumi Okada
et al.

Abstract: Angiocentric glioma (AG) is an extremely rare tumor that often develops in adolescents. Awake surgery for AG occurring in the eloquent area has not been reported to date. We report a case involving a right-handed 15-year-old boy with AG. He presented with a first-time generalized tonic-clonic seizure and was rushed to the local hospital. CT of the head indicated a left frontal low-density mass with no calcification. He was subsequently referred to our hospital. Comparison with a CT scan obtained two years prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Although the literature agrees that this tumor does not enhance after gadolinium administration, in some studies, a slight enhancement with rather mixed signals has been reported [4,8,[19][20][21]28,33,35]. Inside the lesion, it is also possible to observe areas of cystic degeneration [51] (as in our case) and/or calcifications [39,41]. Magnetic resonance spectroscopy also demonstrates increased choline/phosphocreatine and choline/N-acetyl ratios, as well as increased levels of glycine and myoinositol [56].…”
Section: North America 35%supporting
confidence: 64%
See 4 more Smart Citations
“…Although the literature agrees that this tumor does not enhance after gadolinium administration, in some studies, a slight enhancement with rather mixed signals has been reported [4,8,[19][20][21]28,33,35]. Inside the lesion, it is also possible to observe areas of cystic degeneration [51] (as in our case) and/or calcifications [39,41]. Magnetic resonance spectroscopy also demonstrates increased choline/phosphocreatine and choline/N-acetyl ratios, as well as increased levels of glycine and myoinositol [56].…”
Section: North America 35%supporting
confidence: 64%
“…Biopsy was performed in eight cases in total, four being in the brainstem and one being in the thalamus. In four cases, with a follow-up between 5 and 24 months, no recurrence or progression was described [31,35,39,53]. In one case, after the biopsy, the patient made a full recovery and a month later there was no worsening [9].…”
Section: North America 35%mentioning
confidence: 88%
See 3 more Smart Citations